(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
تم تنفيذ البحث في منطقة الغاب ـــ محافظة حماة خلال موسمي الزراعة 2017-2016. استخدم في هذا البحث صنف البطيخ الأصفر الهجين بالميتا ف1 المطعم على الأصلين الأجنبيين، جواد ف1، فورزا ف1، والأصلين المحليين اليقطين Lagenaria siceraria. Mol، والقرع العسلي Cucurbita muschata Duchesne ex Lam. أظهرت النتائج امكانية تطعيم هجين البطيخ الأصفر بالميتا ف1 بنجاح على الأصول، جواد ف1، فورزا ف1، اليقطين البلدي Lagenaria siceraria. Mol، والقرع العسلي Cucurbita muschata. Duchesne ex Lam. وأعطت النباتات المطعمة على الأصول المختلفة زيادة في النمو الخضري، وحقق أصل اليقطين Lagenaria siceraria أكبر طول للساق (211.10)سم، وعدد الفروع (6.04)فرع/نبات، ومساحة المسطح الورقي (14919)سم². كما وجدت زيادة في عدد الأزهار العاقدة (12.26)زهرة عاقدة/نبات، وعدد الثمار (4.14)ثمرة/نبات في النباتات المطعمة على اليقطين Lagenaria siceraria، وأعطت أكبر كمية إنتاج في وحدة المساحة بلغت (5.85)طن/دونم. This investigation was carried out in Al-Ghab, Hama Province during the two agricultural seasons 2016-2017. The experiment was conducted in an open field. This study included considering the yield and resistance of hybrid muskmelon Palmeta F1, grafted on two foreign rootstocks, Jawad F1, Foroza F1 and two local pumpkins Lagenaria siceraria. Mol and Cucurbita muschata. Duchesne ex Lam. The results showed the possibility of successfully grafting the muskmelon F1 on rootstocks, Jawad P1, Forza P1, and Lagenaria siceraria. Mol, and pumpkin Cucurbita muschata. Duchesne ex Lam. Plants grafted on various rootstocks, gave increase of vegetative growth, the rootstock of the pumpkin (Lagenaria siceraria) was the largest length of the stem (211.10) cm, the number of branches (6.04) branch/plant, and the surface of the leafy area (14919) cm². There was also an increase in the number of node flowers (12.26) node /plant, and the number of fruits (4.14) fruit/plant, in plants grafted on the pumpkin (Lagenaria siceraria). And gave the largest amount of production in the unit of area (5.85) tons/dunum.